Preference and calorific value of fuelwood species in rural populations in northwestern Patagonia - Cardoso, María Betina (2015)
Traditional knowledge of fuel species was evaluated, associating species preferences with the physical properties of wood and its combustibility. The physical characteristics of 21 popular firewood species were analyzed in three rural communities in the northwest of Patagonia. Semi-structured interviews were carried out in 91 homes, as well as free listing and walks; samples of the woody species were collected in each of the homes visited. We have hypothesized that the experience of gathering and using fuelwood species, as cognitive know-how, over generations will have enabled local people to know species have best fuel attributes, such as hot coals, low spark and low smoke emission. Thus, for each sample, calorific value, density, moisture content and ash content were measured as predictive variables of combustibility. The fuel attributes of the different woods represent physical properties for which were analyzed by means of the classification for Fuel Value Index (FVI) priority species in the area. Results indicate that the species with the highest FVI values are those mostly preferred by local people such as Berberis microphylla, Prosopis denudans, Schinus johnstonii, Lycium spp., Senecio subulatus and Schinus marchandii. This work recommends the cultivation of energy crops of the preferred native species with high combustibility, to be used as bioenergy and multipurpose species.